Functional Properties of Tilapia Collagen, a Systematic Review Propriedades (Research, Society and Development, 2020)
This systematic review aimed to list the functional properties attributed to collagen obtained from tilapia in scientific studies. The results showed that the antioxidant property is related to the form in which the collagen is presented and the method of antioxidant activity evaluation. It was observed a greater antioxidant activity in the collagen hydrolysate extract obtained from the skin, which plays an important role in the skin chronological aging and in the inhibitory capacity of the photoaging. The functional properties of tilapia collagen hydrolysate should be the object of future analysis in order to complement this research, before integrating them into the list of food or ingredients applicable to the food industry.